(untitled) (GYMNASIUM, 2009)
overcomes the hurdles set by certain training patterns. Progress during the junior period is very important and therefore we consider that strength to power conversion during pre-competition and competition stages can provide adequate strength training in order to achieve remarkable performance. The importance of strength to power conversion was demonstrated by the higher level obtained by the specific and non-specific control events indicators, gradually increasing after successive tests, as well as by the improved results in competition events. The use of strength to power conversion exercises will be administered individually depending on the athlete’s training level, the period or stage of training as well as on the training conditions.